Konfirmationsordningen af 1909 : En undersøgelse og vurdering til belysning af menighedsrådenes allerførste dage. - Iversen, Gertrud (Kirkehistoriske Samlinger, 1988)
In this article the author sets out to analyse the genesis of the Royal Decree for Confirmation of 1909. By examining and describing the enclosed documents of the case, she outlines the various issues and interests at stake in a matter which was subject to theological dispute between the »left-wing« Grundtvigian movement rooted in and centered on the rural population, and the »right-wing« and more pietistically orientated movement, the Indre Mission, which was more engaged in the mission among the urban population. To most people the personal confirmation of their Christian faith had become overshadowed, if not totally ignored by the following feast and family celebration. Opinions differed, however, when it came to solving the matter. Everybody - clergy as well as the laity - could agree on the urgent need of a theological as well as a practical solution to this situation. And a large part of the enclosed documents of the case consists of appeals and suggestions from the laity, i.e. the parochial church councils, to the board of commissioners for a new confirmation service. These appeals were drawn up only one and a half years after the formation and initial gathering af these parochial church councils. Therefore, the auther argues in the present analysis that the Royal Decree for Confirmation of 1909 also sheds light on the early history of one of the principal institutions in Danish religious life in this century: the parochial church council. But even if the initiative for a new confirmation service was taken by the Grundtvigian laity in parochial church councils throughout the country, the analysis shows that the final decree was influenced and drawn up by leaders of the Indre Mission. In a concluding discussion on the matter, the author argues that the plea by the church councils for a free confirmation service was turned down because the large, secularized urban population would lose contact with the church under such an arrangement. Whereas the problem would be solved by the solution empowered by the decree: confirmation without personal confession, thus maintaining the youngsters as a target for the Church’s mission.